Архітектура фортифікацій Галичини середини ХІХ ст. - Піняжко, Тарас Олегович (Національний університет "Львівська політехніка", 2013)
У дослідженні проводиться аналіз феномену галицьких фортифікацій середини ХІХ століття, як унікального явища синтезу військово-оборонної та стилістично-архітектурної думки свого часу. Вперше простежується пов’язаність архітектури капітальних елементів укріплень Галичини цього періоду із пошуком націє-державної тотожності Австрійської імперії в період трансформації сюзеренсько-феодальної суспільної формації у націє-капіталістичну. Також вперше виявляється пов’язаність цих елементів із традиціями ренесансно-венеційського будівництва XVI століття, що на цей час лягли в основу стилізації австрійських військових об’єктів. Сформульовано основні рекомендації із сучасного використання, збереження та адаптації досліджених об’єктів. В исследовании проводится анализ феномена галицких фортификаций середины XIX века, как уникального явления синтеза военного-оборонительной и стилистически архитектурной мысли своего времени. Впервые прослеживается связанность архитектуры капитальных элементов укреплений Галичины этого периода с поиском нация-государственной тождества Австрийской империи в период трансформации сюзеренсько-феодальной общественной формации в нацие-капиталистическую. Также впервые оказывается связанность этих элементов с традициями ренессансно-венецианского строительства XVI века, в настоящее время легли в основу стилизации австрийских военных объектов. Сформулированы основные рекомендации по современному использованию, сохранению и адаптации исследованных объектов. For the first time in Ukrainian science the concept of ‘military architecture’ is formulated and consolidated as a part of scientific and theoretical discourse in the investigation. On the whole the fortifications of Galicia from the middle of the XIX-th century are divided between Polish and Ukrainian survey giving the priority significance to the monuments situated on their territory. A range of problems connected with the consolidation of the concept ‘military architecture’ is defined and personal approach to its formation in the domestic science of architecture is suggested. Thereby it is proposed to differentiate between the so-called ‘negative’ militarism of the postindustrial period and preindustrial ‘positive’ militarism. As well it is suggested to expand the scope of the objects of military architecture by including in it the objects of administrative, supportive and other infrastructure likewise. On investigating 155 fortification elements it is advised to introduce a new classification unit “The Carpathian Defensive Line”. As well the main course of military architecture in the Austrian/Austrian-Hungarian Empire in the middle of the XIX-th century has been defined. On the basis of the analysis of strategic and territorial planning factors it has been suggested to include the fortifications of Olmütz (now Olomouc, Czechia) in the list of Austrian fortifications of the Carpathian line which corresponds to both general logic of defense and more concrete geographical naming within the whole corps of Austrian fortifications. It has been established that the experience of military construction in Northern Italy within the Austrian, Italian and Prussian wars in 1830–1860-s stylistically determined Austrian military architecture. The experience of military construction which took place in the context of transformation of defense objects belonging to the Venetian Republic of the Renaissance period served as the basis of formation of the morphological set of means compiled in the collection of recommended solutions to arrange fortified objects entitled “Lehrbuch der Kriegsbaukunst zum Gebrauche der kais. koen Genie- Akademie”. It has been found out that the mid XIX-th century Galician fortifications became practically the only expression of Venetian-Renaissance style in Austrian military architecture and thus occupy an exceptional position both in the history of Austrian and European heritage. This conclusion only refers to the capital stone formations of Cracow, Olomouc and Lviv as well as the unrealized project of Osvencim fortifications. Three principal methods of modern conservation of the Galician fortification objects of the mid XIX-th century have been suggested. They are adaptive-conceptual, historically significant and informative-supplementary.
Архитектура фортификаций Галичины середины ХІХ века
Architecture of Galician fortifications of middle of 19th century
Keywords: фортифікаційні об’єкти і комплекси; архітектурно-розпланувальна структура; стилевий аналіз; система укріплень; фортификационные объекты и комплексы; архитектурно-распланировочная структура; стилевой анализ; система укреплений; fortification objects and complexes; architectural and planning structure; stylistic analysis; the system of fortifications